(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Although skin diseases have a low mortality rate, they cause significant discomfort and profoundly affect the quality of life and economic status of patients and society. The eastern coastal area of Ca Mau province, Mekong Delta, Vietnam - characterized by a tropical climate, diverse livelihoods, and socioeconomic disparities - creates complex interactions that impact dermatological health and healthcare costs. Objectives: To evaluate the correlation between socioeconomic factors and skin diseases in the eastern coastal area of Hiep Thanh ward, Ca Mau province. Subjects and methods: A descriptive cross-sectional study was conducted on 176 patients with community skin disease. Results: The mean age of patients was 48.5 years (SD 20.4 years). The majority were female (71.1%) and of Khmer ethnicity (51.1%). A total of 18 dermatological conditions were diagnosed, with atopic dermatitis (AD) being the most prevalent (40.7%). AD showed a strong negative correlation (r = -0.199) with household economic autonomy and the strongest positive correlation (r = 0.271) with financial barriers to healthcare access (accounting for 45.5% of obstacles). The rates of self-medication for AD (22.8%, r = 0.161) and non-treatment for scabies (49.1%, r = 0.153) were high, indicating efforts to avoid formal healthcare costs, which inadvertently increase the risk of chronicity and disease transmission. 100% of patients experienced an impact on their quality of life, with a mean DLQI score of 10.7 ± 3.9 (indicating a substantial effect). Psychological burden (low self-esteem, social avoidance) correlated strongly with eczema, scabies, and prurigo (r > 0.154). Ethnic, occupational, and hygiene factors showed strong correlations: the Khmer population had a higher prevalence of scabies (r = 0.203) and prurigo (r = 0.179); occupations such as marine fishing, agriculture, and chemical exposure correlated with seborrheic dermatitis, eczema, and psoriasis, respectively (0.185 < r < 0.325). The use of river/healthy water correlated with scabies and prurigo, while the use of bar soap correlated with folliculitis, and disease duration correlated with asteatotic eczema (r > 0.252). All correlations were statistically significant (p < 0.05 and p < 0.01). Conclusion: The quantitative findings clearly demonstrate the correlation between socioeconomic factors and skin diseases, highlighting root-cause factors (occupation, hygiene, ethnicity) that require intervention in this coastal community.